2017
DOI: 10.1002/ange.201706894
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐kinetic Separation of Rare Earth Elements Using a Redox‐Active Ligand

Abstract: Purification of rare earth elements is challenging due to their chemical similarities. All of the deployed separation methods rely on thermodynamic properties, such as distribution equilibria in solvent extraction. Rare‐earth‐metal separations based on kinetic differences have not been examined. Herein, we demonstrate a new approach for rare‐earth‐element separations by exploiting differences in the oxidation rates within a series of rare earth compounds containing the redox‐active ligand [{2‐(tBuN(O))C6H4CH2}… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…Finally, the proposed effect of Ln III coordination on the E m of PQQ in XoxF 43 suggests the feasibility of performing electrochemical separations of REs using RE-PQQ complexes, as has been accomplished recently with other redox-active ligands. 13 The speciation of aqueous Ln III -PQQ complexes is heterogeneous, 76,77 but such an approach may be possible with the help of PQQ-binding proteins. Another open question is whether lanthanoenzymes that are not PQQ-dependent exist.…”
Section: ■ Lanthanoenzymesmentioning
confidence: 99%
“…Finally, the proposed effect of Ln III coordination on the E m of PQQ in XoxF 43 suggests the feasibility of performing electrochemical separations of REs using RE-PQQ complexes, as has been accomplished recently with other redox-active ligands. 13 The speciation of aqueous Ln III -PQQ complexes is heterogeneous, 76,77 but such an approach may be possible with the help of PQQ-binding proteins. Another open question is whether lanthanoenzymes that are not PQQ-dependent exist.…”
Section: ■ Lanthanoenzymesmentioning
confidence: 99%
“…37 Employing the ability of TriNOx 3− to undergo ligand-based oxidation, we also demonstrated the separation of heavy/heavy RE pairs by an electro-kinetic method. 38 In both cases, the key contributions were the elucidation of a molecular basis to achieve separation of RE pairs. The factor responsible for the exceptional selectivity for some RE pairs of this seminal system, namely, selective selfassociation for light RE pairs, is also its main limitation for extension to other RE pairs, especially for LRE/LRE or HRE/ HRE combinations of REs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…27 Recently, we showed that the use of a tris-hydroxylamine ligand (H 3 TriNOx, tris(2-tert-butylhydroxylamine)benzylamine) 28 displayed differences in the oxidation rates within (RE)-TriNOx complexes modulated by the Lewis acidity of the RE cation, which afforded efficient electro-kinetic separations of RE = Eu, Y, Yb, and Lu (Chart 1). 29 This approach represents a new method for separating RE ions; separations of REs are typically achieved through thermodynamic differences, for example, through differences in affinities for a specific ligand. 30 As such, further development of kinetic-based separations remains a challenging but compelling research opportunity.…”
Section: ■ Introductionmentioning
confidence: 99%